'A Routh O' Auld Nick-Nackets' – the antiquarian collection of John Rae. Issue 1 (March 2015) - Taylor, Paul
Abstract : John Rae, a Scottish antiquarian collector and spirit merchant, played a highly prominent role in the local natural history societies and exhibitions of nineteenth-century Aberdeen. While he modestly described his collection of archaeological lithics and other artefacts, principally drawn from Aberdeenshire but including some items from as far afield as the United States, as a mere 'routh o' auld nick-nackets' (abundance of old knick-knacks), a contemporary singled it out as 'the best known in private hands' (Daily Free Press 4/5/91). After Rae's death, Glasgow Museums, National Museums Scotland, the University of Aberdeen Museum and the Pitt Rivers Museum in Oxford, as well as numerous individual private collectors, purchased items from the collection. Making use of historical and archive materials to explore the individual biography of Rae and his collection, this article examines how Rae's collecting and other antiquarian activities represent and mirror wider developments in both the 'amateur' antiquarianism carried out by Rae and his fellow collectors for reasons of self-improvement and moral education, and the 'professional' antiquarianism of the museums which purchased his artefacts. Considered in its wider nineteenth-century context, this is a representative case study of the early development of archaeology in the wider intellectual, scientific and social context of the era.